2022
DOI: 10.3390/molecules27051476
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Study of Withanosides and Withanolides from Withania somnifera Using Ultra-High Performance Liquid Chromatography-Tandem Mass Spectrometry (UHPLC-MS/MS)

Abstract: Withania somnifera is a traditional Indian herb described under the ‘Rasayana’ class in Ayurveda, which gained immense popularity as a dietary supplement in the USA, Europe, Asia, and the Indian domestic market. Despite enormous research on the pharmacological effect of withanosides and withanolides, bioanalytical method development and pharmacokinetics remained challenging and unexplored for these constituents due to isomeric and isobaric characteristics. In current research work, molecular descriptors, pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
(36 reference statements)
1
16
0
Order By: Relevance
“…Both the test drugs might follow the BCS Class-I nature of one-compartment distribution ( Patil et al, 2014 ), and it is expected to achieve less than <100 μg/ml concentration for the extracts and <100 μM/ml for the individual plant phytoconstituents. It has been verified in in vivo experiments ( Patil et al, 2013 ; Modi et al, 2022 ). Therefore, the K i value can be calculated with the aforementioned formula.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…Both the test drugs might follow the BCS Class-I nature of one-compartment distribution ( Patil et al, 2014 ), and it is expected to achieve less than <100 μg/ml concentration for the extracts and <100 μM/ml for the individual plant phytoconstituents. It has been verified in in vivo experiments ( Patil et al, 2013 ; Modi et al, 2022 ). Therefore, the K i value can be calculated with the aforementioned formula.…”
Section: Methodsmentioning
confidence: 67%
“…Briefly, the Ayurvedic drug properties (rasa, guna, virya, vipaka, and prabhava) are helpful in deciding to use the test drugs and their putative PK-PD approaches [Gogte, 2000;Mishra et al, (Patil et al, 2014), and it is expected to achieve less than <100 μg/ml concentration for the extracts and <100 μM/ml for the individual plant phytoconstituents. It has been verified in in vivo experiments (Patil et al, 2013;Modi et al, 2022). Therefore, the K i value can be calculated with the aforementioned formula.…”
Section: Prediction Of Probable Clinical Interactionsmentioning
confidence: 83%
“…Furthermore, Withaferin A and 1,2deoxywithastramonolide constituents were detectable in plasma up till 10 h which depicted possibility of lower elimination rate for these constituents (Modi et al, 2022).…”
Section: Bioavailabilitymentioning
confidence: 93%
“…The study found reduction in LDL and overall cholesterol levels, increased strength of muscle activity, and normal organ function levels (Raut et al, 2012). Modi et al (2022) performed an ADMET study on Withania somnifera extracts and assessed genotoxicity and mutagenicity at 500 g/kg dose. The ADMET study revealed none of the seven constituents of Withania somnifera extract, including Withaferin A, to be hepatotoxic, mutagenic, or carcinogenic (Modi et al, 2022).…”
Section: Toxicitymentioning
confidence: 99%
See 1 more Smart Citation